POTENTIAL PLANT GROWTH REGULATOR FROM VARIOUS MATERIALS TO PROMOTE PROLIFERATION OF PURPLE SWEET POTATOES (Ipomoea batatas L.) IN ACID SULFATE SOIL - Muhammad Helmy Abdillah; Devi Puspita Sari (Pusat Publikasi Jurnal Universitas Islam Kalimantan, 2026)
The rising demand for purple sweet potato as a functional food commodity necessitates innovative strategies to enhance its growth and yield. One promising approach involves the use of plant growth regulators (PGRs), both natural and synthetic, which play crucial roles in stimulating physiological processes in plants. This study aimed to evaluate the effectiveness of various PGR sources on the growth and productivity of purple sweet potato. The experiment was conducted from January to June 2023 in Sidomakmur Village, Marabahan District, South Kalimantan, using a Randomized Complete Block Design (RCBD) with five replications. Treatments consisted of five types of PGRs: shallot extract, banana corm extract, coconut water, Growtone (synthetic PGR), and water as a control. Each treatment involved the application of 100 mL of solution per experimental unit, totaling 25 experimental units. Observed parameters included sprout emergence time, plant height, leaf number, fresh plant weight, and tuber weight. Data were analyzed using the Least Significant Difference (LSD) test at the 5% significance level. Results showed that banana corm extract significantly accelerated sprout emergence (three times faster) and increased plant height (fourfold) compared to the control. This treatment also produced nearly four times more leaves and fifty-two times heavier tubers than water alone. Meanwhile, the shallot extract showed no significant difference from other treatments in fresh plant weight. These findings suggest both synergistic and antagonistic interactions among the primary phytohormones contained in each material. The study underscores the critical role of organic materials as natural sources of PGRs and nutrients, supporting plant growth and productivity sustainably.